Study on Air Void Characteristics and Hydraulic Characteristics of Porous Asphalt Concrete Based on Image Processing Technology. (14th October 2021) - Wang, Zhanqi; Xie, Jianguang; Gao, Lei; Liu, Yanping; Li, Kuan
Abstract : The appearance of porous asphalt (PA) pavement is to solve the problem of road ponding in rainy days. The internal air voids in PA pavement are the main functional structure that determines its drainage performance. It is of great practical significance to find out the relationship between void drainage capacity and air voids. This paper is aimed at researching the relationship between three-dimensional (3D) pore structures and drainage performance of PA concrete. Four samples were formed and scanned by CT equipment to obtain the internal cross-sectional CT images. Image dodging algorithm and OTSU method were conducted to deal with these CT images for segmenting them into three subimages (void image, asphalt mortar image, and aggregate image) according to the three components of PA concrete. The voids on void images were identified and classified into three groups according to the three kind of pores (interconnected pore, semi-interconnected pore, and closed pore) and reshaped them into 3D pore structures according to the overlapping principle. Then, the volume and size distribution of the pores was analyzed. Besides, this research mainly focused on the influence of several parameters obtained from interconnected pores on the drainage performance of PA concrete at last. The permeability coefficient of PA concrete samples was tested, and equations between permeability coefficient and void content were fitted linearly. The distribution of hydraulic radius and cross-sectional area ratio was calculated and researched by statistical methods. A new parameter, perimeter variation coefficient, is proposed to study the influence of boundary wall roughness on the drainage performance. At last, equivalent drainage channel was drawn to reflect the drainage capacity of PA concrete.